HTLV-1 in Ophthalmology - Kamoi, Koju (Frontiers in Microbiology, 2020)
Human T-cell leukemia virus type 1 (HTLV-1) was the first retrovirus described as a causative agent for human disease. In the field of ophthalmology, a close relationship between HTLV-1 infection and uveitis was identified through a series of clinical and laboratory studies in the late 1980s–1990s. Since then, HTLV-1-related ocular manifestations such as keratoconjunctivitis sicca, interstitial keratitis, optic neuritis and adult T-cell leukemia/lymphoma (ATL)-related ocular manifestations have continuously been reported. During the three decades since the association between HTLV-1 and ocular pathologies was discovered, ophthalmic practice and research have advanced with the incorporation of new technologies into the field of ophthalmology. Accordingly, new findings from recent research have provided many insights into HTLV-1-associated ocular diseases. Advanced molecular technologies such as multiplex polymerase chain reaction (PCR)/broad-range PCR using ocular samples have enabled rapid and accurate diagnosis. Advanced ophthalmic technologies such as widefield fundus camera and optical coherence tomography (OCT) have clarified various features of HTLV-1-associated ocular manifestations, and identified characteristics such as the “knob-like ATL cell multiple ocular infiltration” (KAMOI) sign. Advanced drug delivery methods such as intravitreal injection and sub-Tenon injection have led to progress in preventing disease progression. This article describes global topics and the latest research findings for HTLV-1-associated ocular diseases, with reference to a large-scale nationwide survey of ophthalmologists. Current approaches and unmet needs for HTLV-1 infection in ophthalmology are also discussed.